2021
DOI: 10.1007/s40519-021-01273-7
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic feature of anorexia nervosa: a prospective case–control pilot study

Abstract: Purpose Attention has recently been paid to Clinical Linguistics for the detection and support of clinical conditions. Many works have been published on the “linguistic profile” of various clinical populations, but very few papers have been devoted to linguistic changes in patients with eating disorders. Patients with Anorexia Nervosa (AN) share similar psychological features such as disturbances in self-perceived body image, inflexible and obsessive thinking and anxious or depressive traits. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Specifically, three linguistic indices were found to be more related to this disorder than others: the sensory-somatic words, the prevalence of negative affect, and the RA Intensity Index (MH-IWRAD), which represents the RP disconnection. The presence of emotional disconnection detected in linguistic measures, together with high indices of sensory-somatic words is in line with the literature linking AN to the use of concrete thinking and metaphors, showing a reduction of symbolic capacity and impaired reflective function [ 58 60 ]. Mariani et al [ 37 ] highlighted how language features can be related to a personal expression of psychopathology.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Specifically, three linguistic indices were found to be more related to this disorder than others: the sensory-somatic words, the prevalence of negative affect, and the RA Intensity Index (MH-IWRAD), which represents the RP disconnection. The presence of emotional disconnection detected in linguistic measures, together with high indices of sensory-somatic words is in line with the literature linking AN to the use of concrete thinking and metaphors, showing a reduction of symbolic capacity and impaired reflective function [ 58 60 ]. Mariani et al [ 37 ] highlighted how language features can be related to a personal expression of psychopathology.…”
Section: Discussionsupporting
confidence: 86%
“…The clinical vignettes showed specific linguistic features which connected bodily distress, AN symptoms, and personal emotional conflicts. Linguistic analysis emphasizes the relevance in understanding the relationship between words and emotional activation in psychopathology [ 30 , 37 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical linguistics refers to creating patterns of communication disability concerning a specified illness. Research showed that people suffering from anorexia nervosa compared to healthy people revealed such speech features as concretized emotions (without irony and metaphor), usage of positive words and lower usage of words connected with anxiety, lower level of self-directed attention, little use of firstperson singular sentences, putting sentences mainly in the present tense, narrow range of expression related to the cognitive mechanism, food-related topics were more frequent and few statements were related to the outside world and relations [12].…”
Section: Review Of the Literaturementioning
confidence: 98%
“…Anorexics used a lower number of words per sentence than healthy people, but simultaneously they used more frequently long words (more than six letters). They were less likely to refer to terms pointing to senses (e.g., "see", "feel") and rarely constructed sentences in the present tense [12]. The authors in the second article explored the linguistic markers of differences in Internet self-presentation of selfidentified pro-anorexics who defend anorexia as a lifestyle and self-identified anorexics in recovery.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…A linguistic biomarker is a language-based measure that is associated with a disease outcome or biology in general (Ballman, 2015;Lena, 2021). Some wellknown linguistic biomarkers include: the proportion of pronouns (indicator of depression, Koops et al (2023)), syntax reduction (Anorexia Nervosa, Cuteri et al (2022)), certain lexical and syntactic features (mild cognitive impairment and dementia, Calzà et al (2021); ), and semantic connectedness (schizophrenia, Corcoran et al (2020). Also, the emotions expressed in text have been shown to correlate with mental health diagnosis.…”
Section: Introductionmentioning
confidence: 99%